Observer States and interregional trade between Asia and Latin America - Carlos Enrique Moreno León; Vladimir Rouvinski (Frontiers in Political Science)
This paper seeks to reduce the knowledge gap about the motivation of Asian and Oceanic countries that want to become permanent observers of formal regional integration agreements in Latin America and Caribbean, especially those related to international trade. Using semiparametric cox models, the authors reveal the interest that Asian and Oceanic countries have in observing the State of the rule of law by joining the formalized frameworks that promote international trade in Latin America and the Caribbean as observers. Besides, the paper demonstrates how trade flows from Asia to States that make part of integration agreements in Latin America can influence the decision of Asian nations to seek a permanent observer status. The paper offers clear evidence that the Asian and Oceanic States are inclined to join preferential trade agreements as permanent observers when trade flows from Asian and Oceanic nations toward the members of the regional agreements become important: Asian and Oceanic States wish to protect the trade flows from the new regulations of international commerce that regional blocks may introduce.